Combining weak and strong mutation for a noninterpretive Java mutation system. (24th August 2012) - Kim, Sang‐Woon; Ma, Yu‐Seung; Kwon, Yong‐Rae
SUMMARY Because of the computationally expensive cost of mutation testing, automated system support is indispensable for conducting mutation testing. Mutation systems can be classified into interpretive and noninterpretive, but recent systems are noninterpretive. Weak mutation is a well‐known cost reduction method of mutation testing, but it is not directly applicable to noninterpretive mutation systems. To address the problem and take advantage of the efficiency of weak mutation, this paper presents a combined weak and strong mutation for noninterpretive Java mutation systems. The new term 'serialmutant' is defined as a specialized program to conduct weak mutation against all mutants in an execution and report only weakly killed mutants as strong mutation candidates. Then strong mutation is conducted only for those reported mutants. The paper also describes an implementation based on a previous Java mutation tool, MuJava. Method‐level mutation operators for Java are also redesigned. Experimental results show that the proposed approach efficiently improves the mutation cost in a noninterpretive mutation system. Copyright © 2012 John Wiley & Sons, Ltd.